Study on stainless steel blind bolted T-stub to concrete-filled stainless steel tube connections. (15th April 2022) - Li, Ying-Lei; Zhao, Xiao-Ling
Highlights: Tests on concrete filled stainless steel tubes (CFSST). Tests on T-stub to CFSST connections with various blind bolt types. Finite element analysis of CFSST and T-stub to CFSST connections. Discussion of effects of bolt type, tube thickness and layout of bolts on performance. Formulas to predict the initial stiffness and capacity of CFSST and T-to-CFSST. Abstract: Tension zone of a bolted steel beam-to-column connection can be represented by an equivalent T-stub to column connection under tensile load as recommended in Eurocode 3. This paper presents an experimental and theoretical study on equivalent T-stub to concrete filled stainless steel tube connections (T-to-CFSST) and the basic component (CFSSTs). Both stainless steel blind bolts and normal bolts were selected for the connections. Effects of various parameters, including tube thickness, bolt layout, bolt size, bolt type and bolting method, on the performance of T-to-CFSST and CFSST were investigated. Compared to hollow tubes, filling concrete could greatly enhance the stiffness and strength of the connections. Anchorage between bolts and concrete could be improved by setting studs at bolt ends. A finite element (FE) model was developed in this study and its accuracy was validated by the experimental results. Parametrical study was conducted to investigate the effects of parameters that cannot be covered in experiments, such as material type, tube length and T-stub thickness, on the behavior of CFSST and T-to-CFSST. Based on the experimental and numerical results, theoretical models were proposed to estimate the load–displacement curves of CFSSTs and their stiffness, yield capacity and ultimate capacity. By adopting the concept of component method, formulas were also proposed to predict the stiffness, yield capacity and ultimate capacity of T-to-CFSSTs. In general, the prediction matched well with the experimental results of CFSSTs and T-to-CFSSTs.